2009
DOI: 10.1093/intqhc/mzp027
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of hospital adverse events identified by three widely used detection methods

Abstract: Different detection methods identified different adverse events. Findings are consistent with studies that recommend combining approaches to measure patient safety for internal quality improvement. Potential reported adverse event inconsistencies, low association with documented harm and reporting differences across organizations, however, raise concerns about using these patient safety measures for public reporting and organizational performance comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
151
5
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(172 citation statements)
references
References 18 publications
9
151
5
7
Order By: Relevance
“…The proportion of deaths in intensive care in this study was similar to that of the Canadian study 13 (25%; 95%CI: [19][20][21][22][23][24][25][26][27][28][29][30][31] in that patients with adverse events had higher odds of dying in intensive care. A cohort study carried out in French ICUs identified a positive association between occurrence of two or more adverse events and death (OR = 3.09; 95%CI: 1.30-7.36) 14 .…”
Section: (24 Days Of Icu Stay) the Relationship Betweensupporting
confidence: 74%
See 1 more Smart Citation
“…The proportion of deaths in intensive care in this study was similar to that of the Canadian study 13 (25%; 95%CI: [19][20][21][22][23][24][25][26][27][28][29][30][31] in that patients with adverse events had higher odds of dying in intensive care. A cohort study carried out in French ICUs identified a positive association between occurrence of two or more adverse events and death (OR = 3.09; 95%CI: 1.30-7.36) 14 .…”
Section: (24 Days Of Icu Stay) the Relationship Betweensupporting
confidence: 74%
“…This divergence is in part due to operational differences in adverse event and damage definitions present in the International Classification for Patient Safety (ICPS) 10 on which this study was based. Additionally, the trigger tool proposed by the IHI 25 are considered highly sensitive for identifying events 29 . A study carried out in the United States that combined different strategies verified that 20.2% of patients had adverse events (3.62 adverse events per 100 patients-day) 1 .…”
Section: Discussionmentioning
confidence: 99%
“…7 As with the present study, a previous analysis of the congruence between adverse event reports from health care providers, discharge abstracts and a trigger tool showed that adverse events identified by one method were unlikely to be reported by another. 13 Some of the discrepancy in reports between the two reporting techniques in the study reported here is likely attributable to the reliance of the health care provider reporting system on a passive surveillance technique, whereas the family reporting system involved actively querying each family at the time of the patient's discharge from hospital.…”
Section: Discussionmentioning
confidence: 81%
“…Previous comparisons of results from different methods of finding adverse events (provider self-reports, patient safety indicators [PSIs], global trigger tool [GTT]) concluded that there is very little overlap in the types of events detected by each method and that each approach has strengths and limitations. 26,27 Comparing the results of triggered chart reviews with either PSIs or provider self-reports shows that provider reporting captured more of the events identified with chart review (9 of the 65 events) than those captured by the PSIs calculated on administrative data (2 of the 65). 27 Comparing PSIs and provider reported adverse events produced an interesting pattern in the overlap.…”
Section: Discussionmentioning
confidence: 99%